Lived Experiences of Spa Teachers in Selected Schools of the Division of Misamis Occidental - Sheriel Riah D. Inao; Honeylene Marie Lagas; Emma O. Suana (Future Science / FSH-PH Publications, 2026)
This phenomenological study explored the lived experiences of six teachers in the Special Program in the Arts (SPA) in Misamis Occidental. Data were collected through in-depth interviews and analyzed using Colaizzi’s seven-step method. Findings revealed four major themes: 1) the transformative impact of SPA in preserving culture, enhancing skills, and instilling discipline; 2) challenges caused by limited training, inadequate facilities, and resource shortage; 3) recommendations for holistic learning, extended class hours, teacher training, and more opportunities for competitions; and 4) metaphors that illustrate the teachers’ resilience and passion despite constraints. The study underscores the dynamic role of SPA teachers as both mentors and cultural stewards. It recommends enhanced professional development, improved facilities, and stronger administrative support to sustain the SPA’s contribution to arts education and cultural preservation.